Biology of Pollinator Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) on Oil Palm Plants in Highland Areas - Ayu Andyrah Fitraini; Darma Bakti; Hasanuddin Hasanuddin; Agus Eko Prasetyo; Tjut Ahmad Perdana Rozziansha (Jurnal Agroekoteknologi, 2018)
The objective of the research was to study biology of the Elaeidobius kamerunicus (Coleoptera:Curculionidae) on the oil palm plants in the highlands areas. The research was conducted at PT Perkebunan Nusantara IV Bah Birung Ulu and Laboratory of Plant Pest and Disease Indonesian Oil Palm Research Institute (PPKS) Marihat from November 2016 to April 2017. It was done using by descriptive method. The results showed that the life cycle of E. kamerunicus was 18.6 ± 3.05 days, egg phase, 2.33 ± 0.57 days, the first instar larvae,  2 ± 1.73 days, the second  instar larvae, 5 ± 1 days, and the third instar larvae, 2.66 ± 1.15days and the pupa  4.66 ± 0.57 days. Age of male, 10.72 ± 1.4 days faster than female 14.44  ±1.35 days. Preoviposition period was 2 ± 0 days, while oviposition  9.84 ± 0.96 days, and post oviposition 4 ± 0.89 days. The number of eggs laid by a female during her lifetime was 20.4 ± 2.6. Keywords: Elaeidobius kamerunicus, biology, oil palm, highland areas.